A new species of Tephrosia (Leguminosae-Papilionoideae-Millettieae) from Misiones, Argentina - Queiroz, Rubens Teixeira De; Tozzi, Ana Maria G. A. (Phytotaxa, 2013)
A new species of Tephrosia endemic to Argentina is described and illustrated. Tephrosia fertilis has affinities with T. adunca, based on the type and colour of indumentum, but differs in the relative length of pedicel to bracts, calyx indumentum, presence of a callus and the absence of secretory structure on the standard petal.